Hepatectomy and pneumectomy combined with targeted therapy for primary hepatic neuroendocrine carcinoma: Case report and review of the literature - Huang, Keyu; Lan, Zhujing; Chen, Weitao; Zhang, Jianyong; Wang, Jilong; Zhu, Hai; Xu, Banghao; Zhang, Ling; Lu, Tingting; Guo, Ya; Wen, Zhang (Frontiers in Surgery, 2022)
Primary hepatic neuroendocrine carcinoma (PHNEC) manifests as a rare type of liver tumor. PHNEC is not specifically clinical or radiographical and is often misdiagnosed and mistreated. Here, we present a case report of PHNEC in a 50-year-old woman who was admitted to our department with concealed pain in the right upper abdomen. The initial diagnosis was a probable hepatic space-occupying lesion with tumor bleeding. The patient was subjected to a partial right hemihepatectomy, cholecystectomy, partial resection of the lower lobe of the right lung, partial resection of the diaphragm, and resection of the right perirenal fat sac to alleviate her symptoms. After surgery, gene sequencing was performed to determine the possible cause of the condition. However, five months after discharge, the patient was hospitalized again because of retroperitoneal and peritoneal multiple metastases. Nine months after surgery, the patient died. This case is likely to aid in furthering our understanding of PHNEC to improve the future diagnosis and treatment of this disease.